Alice, I think - Juby, Susan, 1969- (New York : HarperTempest, 2004)
Fifteen-year-old Alice keeps a diary as she struggles to cope with the embarrassments and trials of family, dating, school, work, small town life, and a serious case of "outcastitis.".
"A very different form of this work was previously published in 2000 in Canada by Thistledown Press"--T.p. verso.
Pub Weekly.
School Library Journal.
Wilson's Junior High School.
Young Adult
Keywords: Coming of age -- Fiction; Diaries -- Fiction; Family life -- British Columbia -- Fiction; Psychotherapy -- Fiction; Self-perception -- Fiction; Bildungsromans; Diaries -- Fiction; Family life -- British Columbia -- Fiction; Psychotherapy -- Fiction; Self-perception -- Fiction; British Columbia -- Fiction; British Columbia -- Fiction